Factors associated with unplanned pregnancy among multiparity women in Mosul City - Dalal Thaker Khalil; Salwa Hazem Al-Mukhtar (Genius Journals, 2023)
An unplanned pregnancy is a pregnancy that is either unwanted or the pregnancy is mistimed. It’s also gave many factor that increase the incidence of it. To assess potential factor for unplanned pregnancy among multiparous women
Keywords: assess; incidence; pregnancy; unplanned